THE PERCEPTION STUDY IN KALI BESAR CORRIDOR LANDSCAPE, KOTA TUA JAKARTA - Nanin Pramesti; Eko Adhy Setiawan; Quintarina Uniaty (Universitas Trisakti, 2021)
Organizational activities are influenced by buildings that function as corporate facilities in the Kota Tua area along the Kali Besar corridor, both in the East and West. Apart from the potential for the surrounding buildings in the big river, the open corridor space has not been optimally utilized. Particular problems in the research location, both physical and non-physical, require revitalization. The purpose of this study is to determine the public perceptions of the functions of the activity spaces on the pedestrian path towards the Kali Besar corridor landscape. This investigation employs a qualitative and descriptive model, where the relevant data are obtained using questionnaires. The forms are distributed to various site users with distinct activities, official responsibilities, recreational and commercial interests. Subsequently, the resulting data are carefully analyzed and grouped, before representing the outcomes in tables and graphs. The results show that the user's perception of the Kali Besar corridor landscape is relatively valuable, as evidenced by the responses to the revitalization efforts from 96% of the total respondents. Furthermore, the majority of the visitors were known to support the site restructuring by considering users’ interests.